Labor market policy: A comparative view on the costs and benefits of labor market flexibility - Lawrence M. Kahn (Center for Economic Studies and ifo Institute (CESifo), 2010)
I review theories and evidence on labor market policies and institutions in an international context. These include collective bargaining, minimum wages, employment protection laws, unemployment insurance (UI), mandated parental leave, and active labor market policies. Scandinavia and Central Europe follow more interventionist policies than Canada, the UK and the US. Vulnerability to external market forces and ethnic homogeneity may explain such differences. While the interventionist model appears to reduce wage inequality and raise job security for incumbent workers, it also often relegates new entrants (disproportionately women, youth and immigrants) and the less skilled to temporary jobs or unemployment.
Keywords: J08; J68; 330; labor market flexibility; Arbeitsmarktflexibilisierung; Arbeitsmarktpolitik; Institutionalismus; Vergleich; Lohnstruktur; Beschäftigung; Welt